'A La Mode De Bourgoigne?' The 'Burgundian' Ceremonial at the Court of Albert and Isabella in Brussels (1598–1621). (2nd January 2019) - Raeymaekers, Dries
ABSTRACT: In 1599 the Archdukes Albert and Isabella introduced a new ceremonial at their court in Brussels. Cobbled from the model that was in vogue at the royal court of Madrid, it was known as the 'Burgundian' ceremonial, as its origins could be traced back to the renowned court of the Dukes of Burgundy during whose reign the court of Brussels had thrived as never before. Strangely, the reforms met plenty of criticism among the courtiers, who accused the archdukes of putting aside time-honoured local traditions. The 'Burgundian' ceremonial was experienced by the Netherlandish nobility not only as 'new' but also as 'foreign', indicating that it was no longer recognizable as a direct derivative of the age-old tradition in Brussels. This article examines the origins of the ceremonial at the archducal court and shows how and why it came to deviate from the model that had traditionally been maintained in the Burgundian Netherlands.